Supplement Consumption among Post stroke Patients in Dr. Hasan Sadikin General Hospital Bandung - Rahayu, Annisa; Novitri, Novitri; Utami, Novi Vicahyani (Althea Medical Journal, 2016)
Background: Stroke is one of the leading causes of global disability. Post stroke rehabilitation program becomes the key to gain functional recovery. Thus it minimizes disabilities. Multiple studies have been carried out to gain greater functional outcomes for post stroke patients, including medical therapy such as supplements. However, supplement effectiveness in providing stroke recovery or prevention is still debatable. There is no data of supplement consumption among post stroke patients; therefore, the aim of this study was to determine the supplement consumption among post stroke patients.Methods: This study was a cross sectional descriptive study using primary data with a consecutive sampling method. Minimum samples for this study were 42 post stroke respondents who followed rehabilitation program. This study was conducted at Physical Medicine and Rehabilitation Clinic of Dr. Hasan Sadikin General Hospital Bandung from June until November 2013. The interviews were done after written informed consent was obtained. Descriptive statistics such as frequency distributin and proportion were used to analyze the data.Results: From 42 respondents, 23 (55%) respondents consumed the supplement. From 34 supplements recorded, 56% were herbs supplements; followed by multivitamin (29%), mineral (6%), multivitamin and mineral (6%), and other supplement (3%). The most frequent ingredients composed in the supplements were B1, B6 and B12 vitamin (7%).Conclusions: More than a half of post stroke patients at Physical Medicine and Rehabilitation Clinic Dr. Hasan Sadikin General Hospital are supplement users, with herbal supplements as the majority. The most frequent ingredients used are B1, B6 and B12 vitamin. [AMJ.2016;3(3):451â8]DOI: 10.15850/amj.v3n3.865